Proteolytic Activity of the Activator Produced by Streptokinase in Human Plasma - Claeys, H; Amery, A; Verhaeghe, R (Thrombosis and Haemostasis, 1971)
In the in vitro activation of the fibrinolytic system of human plasma by streptokinase (SK) maximal caseinolytic and fibrinogenolytic activity was found at a SK concentration of 2.103 u/ml plasma. At higher concentrations of SK these activities decrease and level off to a plateau at a SK concentration of 105 u/ml plasma for the caseinolytic activity and 104 u/ml plasma for the fibrinogenolytic activity. At these high SK concentrations the caseinolytic and fibrinogenolytic activity can not or only slightly be inhibited by soybean trypsin inhibitor at concentrations, which completely inhibit these activities at lower SK concentrations. The bovine plasminogen activator activity increases with increasing SK concentrations between 103 and 106 u SK/ml plasma. No plateau of maximal activator activity could be demonstrated. It is suggested that the remaining fibrinogenolytic and caseinolytic activity at high SK concentrations is not due to plasmin activity, but that the bovine plasminogen activator has direct caseinolytic and fibrinogenolytic activity.